Strategies for Preserving Value Amidst Inflationary Periods : Insights from the past 20 years - Skornik, Maciej; Pekárek, Štěpán; Zeman, Mikuláš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
Paraphrasing Benjamin Franklin, there are three certainties in life: death, taxes, and inflation. While inflation cannot be completely eradicated, it can be managed. This thesis explores all the different investment methods aimed at preserving the value of one’s portfolio during periods of high inflation, focusing on the United States in the years 2004 to 2023. The study evaluates various assets derived from different economic sectors, including stock indices (S&P 500 and Nasdaq Composite), bonds (U.S. Treasuries), commodities (gold), real estate (Case-Shiller Index), and Treasury Inflation-Protected Securities (TIPS). This thesis analyzes their performance across all the key inflationary regimes, most notably the Global Financial Crisis and the post-COVID period, and a broader 20-year horizon for a more general overview. This paper utilizes mechanisms such as the Capital Asset Pricing Model (CAPM), GARCH models, and regression analysis. It focuses on risk-adjusted returns, volatility, and the assets' correlation with inflation. All assessments are conducted within the U.S. dollar framework. The results of this paper indicate that in high inflation regimes, investing in real assets such as gold, TIPS, or real estate can substantially improve the shielding capability of a portfolio from inflation as opposed to a traditional fixed stock-bond portfolio. These insights provide guidance for investors seeking to hedge against inflation and optimize their portfolio performance.
Vedoucí práce: Štěpán Pekárek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses